2022
DOI: 10.3389/fmicb.2022.987462
|View full text |Cite
|
Sign up to set email alerts
|

Diversity, structure, and distribution of bacterioplankton and diazotroph communities in the Bay of Bengal during the winter monsoon

Abstract: The Bay of Bengal (BoB) is conventionally believed to be a low productive, oligotrophic marine ecosystem, where the diazotroph communities presumed to play a vital role in adding “new” nitrogen through the nitrogen fixation process. However, the diazotroph communities in the oceanic region of the BoB are still poorly understood though it represents most of the seawater volume. The present study investigated a detailed account of the bacterioplankton community structure and distribution in the oceanic BoB durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 94 publications
(138 reference statements)
0
4
0
Order By: Relevance
“…To date, there are no reports on the abundance of Prochlorococcus in the coastal waters of Kochi [58]. Similar community structure has been previously observed during winter monsoon period of Bay of bengal in which Proteobacteria represented the highest diversity and largest fractions [59]. Candidatus Nitrosopelagicus, Nitrosopumilus show increased abundance from south to north.…”
Section: Taxonomic Distribution During Pmsupporting
confidence: 65%
“…To date, there are no reports on the abundance of Prochlorococcus in the coastal waters of Kochi [58]. Similar community structure has been previously observed during winter monsoon period of Bay of bengal in which Proteobacteria represented the highest diversity and largest fractions [59]. Candidatus Nitrosopelagicus, Nitrosopumilus show increased abundance from south to north.…”
Section: Taxonomic Distribution During Pmsupporting
confidence: 65%
“…A recent study showed that gammaproteobacterial diazotrophs are negatively influenced by temperature during the NEM in the BoB and positively correlated with silicate, suggesting a possible association with diatoms (Shao and Luo 2022). Instead, in the BoB alpha‐ and betaproteobacterial diazotrophs are positively correlated to temperature (Wu et al 2022).…”
Section: Distribution and Diversity Of Diazotrophs In The Indian Oceanmentioning
confidence: 99%
“…In other seasons, the BoB harbors cyanobacterial representatives including Trichodesmium (particularly during the IM), Richelia , Katagnymene , UCYN‐A, and UCYN‐B. Because Trichodesmium typically grows in oligotrophic and stratified epipelagic waters (Capone et al 1997), the high turbulence and strong wind conditions observed in the BoB during the NEM and SWM may be unfavorable for their growth (Wu et al 2022). While cyanobacteria predominate at the surface, alpha‐ and betaproteobacteria are significantly more abundant at deeper levels (based on the relative abundance of ASVs) (Appendix S2; Fig.…”
Section: Distribution and Diversity Of Diazotrophs In The Indian Oceanmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, the microbial communities at the foundation of the BoB ecosystem remain poorly understood. A few recent studies have looked at bacterial diversity through 16S amplicon sequencing, but very few have looked at the functional potential and interactions of the microbial communities in this region ( 10 , 11 ). Among the studies that have attempted to look at microbial diversity through metagenomics, all have been focused on sediment bacteria in the deep sea ( 12 ), with little or no efforts targeted toward understanding the microbiota of surface water communities, the communities closely associated with corals, seagrass, and mangroves using similar approach.…”
Section: Introductionmentioning
confidence: 99%